Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thi nking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study